Nomenclatural changes and two new species in the leafhopper genus Usanus DeLong (Hemiptera: Cicadellidae) with notes on conservation status - Pinedo-Escatel, J. Adilson; Dietrich, Christopher H. (Zootaxa, 2020)
The Mexican leafhopper genus and species Devolana hemicycla DeLong, 1967 syn. nov., is recognized as a junior synonym of Usanus stonei DeLong, 1947. Three previously described species, U. tuxcacuensis (Pinedo-Escatel & Aguilar-Pérez, 2019) comb. nov., U. youajla (Pinedo-Escatel, 2019) comb. nov., and U. xajxayakamej (Pinedo-Escatel, 2019) comb. nov. are transferred to Usanus. Two new species, U. xochipalensis sp. nov. and U. igualaensis sp. nov. from Guerrero, are described and illustrated. An updated key to all known species of Usanus is provided.